Optimising Cervical Cancer Screening: A Critical Review of Quality Control, Assurance, and Process Improvement Strategies in Pap Smear Cytology - Gracy Jeba Rani; S Sowmya; ES Keerthika Sri (Journal of Clinical and Diagnostic Research)
Cervical cancer is a significant global health concern, with the Pap smear serving as a crucial tool for early detection. However, the effectiveness of Pap smear screening is compromised by false positives and negatives, necessitating robust Quality Control (QC) and Quality Assurance (QA) measures. This review examines the preanalytical, analytical, and post-analytical phases of Pap smear cytology, focusing on quality indicators that enhance diagnostic accuracy. The 2014 refinement of the Bethesda System for Reporting Cervical Cytology (BSRCC) provides a standardised framework for classifying cytological abnormalities. Key quality indicators, such as the ASCUS/SIL ratio and Cytology-Histology Concordance (CHC), are highlighted, along with the importance of Six Sigma metrics and Lean principles for evaluating and improving Pap smear procedures. The review emphasises the implementation of QC, QA, Six Sigma, and Lean principles in healthcare systems to ensure high diagnostic standards, operational efficiency, and patient safety.